4, 4′-Biphenyldisulfonic acid induced coordination polymers of symmetrical tetramethyl cucurbit[6]uril with alkaline-earth metals for detection of antibiotics. Issue 6 (18th January 2023) - Chen, Kai; Zhu, Zhao-Qiang; Zhang, Ming-Hui; Yang, Xiang; Li, Jie; Chen, Chen; Redshaw, Carl
Abstract : Three new 3D TMeQ[6]-based coordination polymers of alkali-earth metal ions (Ca 2+, Sr 2+ and Ba 2+ ) were characterized, and one can highly selectively detect NFX (norfloxacin) molecules via a fluorescence quenching effect. Abstract : Three new coordination polymers based on macrocyclic symmetrical tetramethyl cucurbit[6]uril (TMeQ[6]) with formulae [Ca2 (C40 H44 N24 O12 )(H2 O)10 ](C12 H8 O6 S2 )2 ·13H2 O (1 ), [Sr(C40 H44 N24 O12 )(H2 O)4 ](C12 H8 O6 S2 )·13H2 O (2 ), and [Ba2 (C40 H44 N24 O12 )(C12 H8 O6 S2 )](C12 H8 O6 S2 )(H2 O)7 ·12H2 O (3 ) have been obtained by the self-assembly of TMeQ[6] with the corresponding alkaline-earth metal salts in the presence of 4, 4′-biphenyldisulfonic acid (H2 BPDS). Single crystal X-ray diffraction analysis of these three coordination polymers reveals that the deprotonated 4, 4′-biphenyldisulfonic acid (H2 BPDS 2− ) plays an important role in the self-assembly of these coordination polymers. In complexes 1 and 2, only the TMeQ[6] is involved in coordination with the Ca 2+ and Sr 2+ ions. The BPDS 2− is involved in "outer-surface interactions" with the TMeQ[6]. Meanwhile, in complex 3, the BPDS 2− is also coordinated with the Ba 2+ ion. These coordination polymers provide a new strategy to design and construct Q[ n ]-based poly-dimensional coordination polymers, which can be built by one-dimensional Q[ n ]-metal coordination chains via outer-surface interactions. Furthermore, complex 1 can detect NFX (norfloxacin) molecules with high selectivity.